Genetic factors associated with patient-specific warfarin dose in ethnic Indonesians - Suriapranata, Ivet M (BioMed Central, 2011)
BACKGROUND: CYP2C9 and VKORC1 are two major genetic factors associated with inter-individual variability in warfarin dose. Additionally, genes in the warfarin metabolism pathway have also been associated with dose variance. We analyzed Single Nucleotide Polymorphisms (SNPs) in these genes to identify genetic factors that might confer warfarin sensitivity in Indonesian patients. METHODS: Direct sequencing method was used to identify SNPs in CYP2C9, VKORC1, CYP4F2, EPHX1, PROC and GGCX genes in warfarin-treated patients. Multiple linear regressions were performed to model the relationship warfarin daily dose requirement with genetic and non-genetic variables measured and used to develop a novel algorithm for warfarin dosing. RESULTS: From the 40 SNPs analyzed, CYP2C9 rs17847036 and VKORC1 rs9923231 showed significant association with warfarin sensitivity. In our study population, no significant correlation could be detected between CYP2C9*3, CYP2C9C-65 (rs9332127), CYP4F2 rs2108622, GGCX rs12714145, EPHX1 rs4653436 and PROC rs1799809 with warfarin sensitivity. CONCLUSIONS: VKORC1 rs9923231 AA and CYP2C9 rs17847036 GG genotypes were associated with low dosage requirements of most patients (2.05 ± 0.77 mg/day and 2.09 ± 0.70 mg/day, respectively). CYP2C9 and VKORC1 genetic variants as well as non-genetic factors such as age, body weight and body height account for 15.4% of variance in warfarin dose among our study population. Additional analysis of this combination could allow for personalized warfarin treatment in ethnic Indonesians.